Effect of element substitution and surface treatment on low temperature properties of AB3.42-type La–Y–Ni based hydrogen storage alloy. (19th January 2021) - Zhou, Shujuan; Zhang, Xu; Wang, Li; Zhao, Yuyuan; Xiong, Wei; Li, Baoquan; Li, Jin; Xu, Jin; Yan, Huizhong
Abstract: The low-temperature performance (LTP) of AB3.42 -type La–Y–Ni hydrogen storage alloy was studied by methods of element substitution and surface treatment. The effect of Mn-additive on LTP of La1·3 Ce0·5 Y4·2 Ni19.5- x Mn x Al ( x  = 0, 0.2, 0.5) was systematically investigated. Electrochemical studies showed that Mn-additive deteriorated the LTP of the alloy by reducing platform pressure, deteriorating kinetic performance and forming more oxides on the alloy surface. RE-substitution and hot alkali-ultrasonic treatment of La1.3 RE0.5 Y4·2 Ni19·5 Al (RE = Ce, Sm, Nd) alloys were applied to further optimize the LTP. The maximum discharge capacity and capacity retention at the 100th cycle of La1·3 Ce0·5 Y4·2 Ni19·5 Al alloy were 252.1 mA h/g and 87.1% at 243 K, respectively. Furthermore, the LTP of RE-substitution alloys at 243 K was conspicuously improved by surface treatment, which were raised from 214.7 mA h/g to 301.1 mA h/g by Sm-substitute, from 220.9 mA h/g to 303.9 mA h/g by Nd-substitute and from 252.1 mA h/g to 254.8 mA h/g by Ce-substitute. Highlights: The Ce2 Ni7 and Gd2 Co7 -type phase own diverse electrochemical characteristics under different temperatures. Mn-additive reveals negative effect on the low temperature dischargeability of the alloy. Surface treatment promotes the low temperature dischargeability of the Mn-free alloy.